Beyond Germs : Native Depopulation in North America - Cameron, Catherine M.; Kelton, Paul; Swedlund, Alan C. (Book collections on Project MUSE., 2015)
"Beyond Germs challenges the hypothesis that the massive depopulation of the New World was primarily caused by diseases brought by Europeans, which scholars used for decades to explain the decimation of the indigenous peoples of North America. Contributors argue that blaming germs downplays the active role of Europeans in inciting wars, destroying livelihoods, and erasing identities"--Provided by publisher.